THE EFFECTS OF THE REACTIONARY THOUGHT IN THE PRESENT ERA (Islamic Sciences Journal, 2023)
Praise be to God and prayers and peace be upon the Messenger of Allah ... As forGod sent Muhammad to bring people out of the darkness to the light, and humanity was in dire need of God Almighty says: "God looked to the people of the earth Vmgthm, Arabs and Ajmhm only remnants of the people of the book," was his mission mercy to the worldsHe sent him to obey his command and follow his footsteps and imitate him as the Almighty says: {And we sent from a messenger only to obey the permission of God}The Prophet (peace and blessings of Allaah be upon him) gave his companions to respond to the texts of revelation without hesitation. Allaah says (interpretation of the meaning): Life, the universe was awakened by revelation and the earth shone with the light of its Lord But the weakness, degeneration, division, and dispersion of this nation is an inevitable result of the stochastic and scientific situation that they have reached. The doctrine has great implications in the lives of individuals and nations, but it varies according to the same faith and the extent of its authority over the soulsReasons for choosing the topic:1. Delay is one of the most perverse in the history of Muslims, which left a serious impact is still visible so far.2. This thought started with a casual suspicion and a passing word, and then developed until the latest reality is a serious and dangerous deviation, and perhaps the founders of this thought has never been born of what can be derived from the view that was presented to them and that which they suspected.3. Seeking to purify the correct Islamic faith, which is similar to that of bid'ah and its mixed deviations.* In this research I used the inductive and analytical method, and divided it into an introduction, a preface, two papers, a conclusion and indexes.
Keywords: Deferred - deferment - effects of deferment .